2014
DOI: 10.1016/j.jviscsurg.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green fluorescence imaging in the surgical management of liver cancers: Current facts and future implications

Abstract: Imaging detection of liver cancers and identification of the bile ducts during surgery, based on the fluorescence properties of indocyanine green, has recently been developed in liver surgery. The principle of this imaging technique relies on the intravenous administration of indocyanine green before surgery and the illumination of the surface of the liver by an infrared camera that simultaneously induces and collects the fluorescence. Detection by fluorescence is based on the contrast between the (fluorescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 35 publications
1
66
0
2
Order By: Relevance
“…The exact optimal dosage and timing still remains to be defined. 7,29 Technical aspects and historical context of ICG fluorescence are well reported in the review by Reinhart et al, 30 but pathophysiological mechanisms of ICG secretion are not totally elucidated. 31 Possible uses in oncological surgery are summarized in two reviews.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact optimal dosage and timing still remains to be defined. 7,29 Technical aspects and historical context of ICG fluorescence are well reported in the review by Reinhart et al, 30 but pathophysiological mechanisms of ICG secretion are not totally elucidated. 31 Possible uses in oncological surgery are summarized in two reviews.…”
Section: Discussionmentioning
confidence: 99%
“…7,29 On the other side, many advantages are described in detection of small nodules unknown before surgery with a statistical significant difference compared to intra-operative ultrasound. 9,13,19,21 Ishizawa et al 9 showed in their report that 13% of lesions were not evident unless observed by ICG fluorescent imaging.…”
Section: Detection and Characterization Of Surface Liver Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…ICG is a fluorescent marker that is excited at a wavelength between 600 and 900 nm to emit maximum fluorescence at 810 nm in water and 830 nm in blood. ICG was particularly used in previous studies [13,17] to improve lymph node mapping and enhance tumor contrast. Infrared fluorescence endoscopy with ICG has been used to observe GI vascular structure and may provide precancerous information [12].…”
Section: Introductionmentioning
confidence: 99%
“…Removal of intracranial gliomas under 5-ALA guidance has demonstrated that the real extension of the tumour is likely to be beyond that identified by MRI (1). Equally good, several research articles have attested to the added value of ICG/NIR for precisely locating liver tumours, intraoperatively (2). Furthermore, boosting precision of cancer localization can be achieved by selective targeting where the fluorophore is bound to a molecule that has avidity for certain neoplastic tissue.…”
mentioning
confidence: 99%